Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1990
DOI: 10.1177/0148607190014005501
|View full text |Cite
|
Sign up to set email alerts
|

Enteral Nutrition in the Early Postoperative Period: A New Semi‐Elemental Formula Versus Total Parenteral Nutrition

Abstract: Several studies have reported that gastrointestinal (GI) intolerance symptoms are the limiting factor to enteral alimentation in the immediate postoperative period and often the reason for resorting to total parenteral nutrition (TPN). We postulated that Reabilan HN (a recently developed small peptide-based formula, in part obtained by enzyme hydrolysis of proteins) might be better absorbed and better tolerated so as to avoid the need for TPN. Accordingly, 19 patients undergoing major abdominal surgery were ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
4

Year Published

1997
1997
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(36 citation statements)
references
References 21 publications
0
32
0
4
Order By: Relevance
“…Heylen et al 69 NR NR NR Hamaoui et al 76 Random number table NR NR Schroeder et al 39 NR NR Intention-to-treat Binderow et al 72 NR NR NR Reissman et al 37 NR NR NR Baigrie et al 70 NR NR NR Beier-Holgersen et al 12 NR Yes Intention-to-treat Braga et al 27 NR 31 NR NR Intention-to-treat Heslin et al 32 Randomization using sealed envelopes NR Intention-to-treat Reynolds et al 38 NR NR Intention-to-treat Sand et al 40 NR NR Intention-to-treat Shirabe et al 42 NR NR Intention-to-treat Watters et al 44 Randomization …”
Section: Studymentioning
confidence: 99%
“…Heylen et al 69 NR NR NR Hamaoui et al 76 Random number table NR NR Schroeder et al 39 NR NR Intention-to-treat Binderow et al 72 NR NR NR Reissman et al 37 NR NR NR Baigrie et al 70 NR NR NR Beier-Holgersen et al 12 NR Yes Intention-to-treat Braga et al 27 NR 31 NR NR Intention-to-treat Heslin et al 32 Randomization using sealed envelopes NR Intention-to-treat Reynolds et al 38 NR NR Intention-to-treat Sand et al 40 NR NR Intention-to-treat Shirabe et al 42 NR NR Intention-to-treat Watters et al 44 Randomization …”
Section: Studymentioning
confidence: 99%
“…Early enteral feeding appears to attenuate part of the stress response in particular groups of patients. This has been demonstrated in animal studies and a few small patient studies [4][5][6]. The ability to manipulate the patient's immune response using specific enteral nutrients (immunonutrition) has also provoked considerable interest [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Studies of 100% WHP and Crohn's disease are characterized in Table 1 [5,10,11,[13][14][15][16][17][18][19][20][21][22][23][24][25] . In a one year prospective study, six Crohn's disease patients (median age, 13.6 years) were treated with an isotonic, 100% WHP semielemental diet to evaluate growth parameters and disease activity measures [11] .…”
Section: Crohn's Diseasementioning
confidence: 99%
“…As a result, studies have suggested improved growth and development patterns, fewer gastrointestinal complications, improved visceral protein levels, and decreased rates of mortality. Studies of patients with Crohn's disease, pancreatitis, and human immnodeficiency virus (HIV) among other conditions have shown improved nutrition status and clinical outcomes from supplemental semielemental formulas [9][10][11][12] . The purpose of this review is to comprehensively summarize the scientific and clinical evidence of 100% whey-hydrolyzed protein (WHP) semielemental diets and nutritional and health outcomes across various nutritionally-vulnerable populations.…”
Section: Introductionmentioning
confidence: 99%